2017
DOI: 10.1002/mus.25994
|View full text |Cite
|
Sign up to set email alerts
|

French translation and cross‐cultural adaptation of The Myotonic Dystrophy Health Index

Abstract: The French version of the MDHI is an optimal translation of the original instrument that is acceptable to native patients and ready for clinical trial use. Muscle Nerve 57: 686-689, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…In fact, disease perception is one of the determinants of psychological distress and/or coping [ 7 , 33 ]. Therefore, although definitive evidence for the effectiveness of psychosocial interventions to improve disease perception in patients with muscular diseases is unavailable [ 34 ], it is plausible that psychosocial interventions could optimize QoL in these patients [ 35 , 36 ]. A large international study demonstrated that cognitive behavior therapy for patients with myotonic dystrophy improved physical activity and participation, but it did not improve their QoL and disease burden [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, disease perception is one of the determinants of psychological distress and/or coping [ 7 , 33 ]. Therefore, although definitive evidence for the effectiveness of psychosocial interventions to improve disease perception in patients with muscular diseases is unavailable [ 34 ], it is plausible that psychosocial interventions could optimize QoL in these patients [ 35 , 36 ]. A large international study demonstrated that cognitive behavior therapy for patients with myotonic dystrophy improved physical activity and participation, but it did not improve their QoL and disease burden [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Myotonic Dystrophy Health Index (MDHI) is a disease-specific patient reported outcome measure designed specifically for use in myotonic dystrophy clinical trials [6,7]. It has been identified during OMMYD-2 [3] as potentially interesting and was translated into French and Italian at this time [8,9]. Given the prior validation of this instrument, it has been identified by the NIH's Common Data Elements group as one of only four outcome measures that are highly recommended for use in DM1 studies and the only outcome measure that is highly recommended as an outcome/endpoint to measure multifactorial patient reported Burden of Disease.…”
Section: Outcome Measures Myotonic Dystrophy Health Indexmentioning
confidence: 99%
“…First, although the INQoL covers the major components of QoL for patients with DM1, the relative importance of contributing factors could be affected by the underlying concept of QoL measured. Recently, the Myotonic Dystrophy Health Index, which measures the burden of disease in myotonic dystrophy, is available and has been validated in several languages [33][34][35][36]. The INQoL is rather a measure of how disease symptoms impact on the patient's perspective.…”
Section: Limitationsmentioning
confidence: 99%